Improving patient outcomes in hereditary angioedema: reducing attack frequency using routine prevention with C1 inhibitor concentrate. (21st May 2014) - Dominas, Nina; Hoffmann, Thomas K; Bas, Murat; Greve, Jens
Abstract : Hereditary angioedema (HAE) is a rare inherited disorder, characterised by recurrent oedema attacks in various regions of the body. In HAE, mutations in the C1 esterase inhibitor (C1-INH) gene result in decreased C1-INH concentrations (type I HAE) or functionally deficient C1-INH (type II HAE), leading to inappropriate activation of the kallikrein–kinin system and release of vasoactive mediators. Treatment of HAE aims to manage acute attacks (using replacement C1-INH or bradykinin B2 receptor antagonist) or prevent attacks through prophylaxis (using C1-INH or attenuated androgens). We present a case of a 67-year-old man with HAE who suffered a high number of breakthrough HAE attacks while undergoing long-term prophylaxis with attenuated androgens. Androgen therapy was safely discontinued and routine prevention therapy with C1-INH (1000 U) introduced as part of an individualised management approach, in line with published clinical trial data, which improved patient outcomes in terms of HAE attack frequency and severity.